2019
DOI: 10.5830/cvja-2018-069
|View full text |Cite
|
Sign up to set email alerts
|

The role of echocardiography in acute viral myocarditis

Abstract: The diagnosis of acute viral myocarditis can be very challenging during the initial evaluation, warranting multiple diagnostic tests to be performed, including a full echocardiographic evaluation to exclude other aetiologies that might present similarly. Acute myocarditis may masquerade as acute myocardial infarction in older patients or as any form of cardiomyopathy in young patients. As a result, all these patients need a thorough evaluation and to be managed at a high cardiac-care setting from the very outs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 28 publications
1
7
0
Order By: Relevance
“…Griffin found the viral spectrum of VMC in myocardial specimens was mostly HAdV, followed by HEV, as well as CMV and HSV [11]. Finally, VMC caused by multiple viruses is also more common than before [6,12]. The results of our study showed that among the patients with VMC, a co-infection of HHV-6/7 and Parvovirus B-19 was found in the one patient.…”
Section: Discussionsupporting
confidence: 48%
“…Griffin found the viral spectrum of VMC in myocardial specimens was mostly HAdV, followed by HEV, as well as CMV and HSV [11]. Finally, VMC caused by multiple viruses is also more common than before [6,12]. The results of our study showed that among the patients with VMC, a co-infection of HHV-6/7 and Parvovirus B-19 was found in the one patient.…”
Section: Discussionsupporting
confidence: 48%
“…Echocardiography is an essential part of myocarditis diagnostics that helps assess LV function and eliminate other causes of heart failure. 58,59 Previous studies have also illustrated that in Covid-19 patients with myocardial injury, echocardiography often reveals normal to mildly reduced LVEF along with mild RV failure. 60,61 Despite the fact that non-specific findings are seen on echocardiograms in myocarditis, a comprehensive review of the results may help to indicate a diagnosis, initial management, and to evaluate prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…The bulk of patients in this review exhibited reduced LVEF and pleural effusion on echocardiogram. Echocardiography is an essential part of myocarditis diagnostics that helps assess LV function and eliminate other causes of heart failure 58,59 . Previous studies have also illustrated that in Covid‐19 patients with myocardial injury, echocardiography often reveals normal to mildly reduced LVEF along with mild RV failure 60,61 .…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned above, ECG has a key role in the assessment of severity. Of note, UCG, whose diagnostic criteria have been suggested and adopted for myocarditis patients, may also be used to distinguish FM from myocarditis (23,24). In the near future, the role of UCG in myocarditis patients we be further studied.…”
Section: Discussionmentioning
confidence: 99%